2002
DOI: 10.1152/ajpheart.00725.2001
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor activation at medullary sympathetic neurons contributes to postexercise hypotension

Abstract: A single bout of exercise results in a postexercise hypotension (PEH) that is accompanied by a reduced baroreflex function. Based on the role of rostral ventrolateral medulla (RVLM) neurons in controlling sympathetic nerve activity (SNA) and blood pressure, the role of gamma-aminobutyric acid (GABA) in controlling RVLM neuronal activity, and the reduced baroreflex-SNA relationship during PEH, we determined whether: 1) RVLM neuronal activity is decreased during PEH, 2) GABA(A)-receptor mechanisms mediate the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 58 publications
4
37
2
1
Order By: Relevance
“…In support of this, it has been shown that resting SNA and gain of baroreflex SNA control are reduced after prolonged elevations of arterial pressure (32). Consistent with the results of previous studies (10,11,32,33), in the present study SBP-LFamp, a marker of SNA (18), decreased in association with a reduction of arterial pressure after exercise as well as Iso+Phe infusion. On the other hand, BRS, which is predominantly determined by augmentation in cardiac vagal activity, increased after exercise but not after cessation of Iso+Phe infusion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In support of this, it has been shown that resting SNA and gain of baroreflex SNA control are reduced after prolonged elevations of arterial pressure (32). Consistent with the results of previous studies (10,11,32,33), in the present study SBP-LFamp, a marker of SNA (18), decreased in association with a reduction of arterial pressure after exercise as well as Iso+Phe infusion. On the other hand, BRS, which is predominantly determined by augmentation in cardiac vagal activity, increased after exercise but not after cessation of Iso+Phe infusion.…”
Section: Discussionsupporting
confidence: 93%
“…Apart from these chronic effects of exercise, a single bout of dynamic exercise is known to induce hypotension in the post-exercise period in hypertensive subjects (3) and spontaneously hypertensive rats (SHR) (4)(5)(6). Post-exercise hypotension (PEH) is associated with no change or a reduction of heart rate (HR) (7,8) and a reduction in cardiac (9) and peripheral sympathetic nerve activity (10,11). The reduction in blood pressure without a baroreflex-mediated compensatory tachycardia or sympa-thetic excitation suggests that a single bout of dynamic exercise resets the operating point of the arterial baroreflex to a lower pressure (5).…”
Section: Introductionmentioning
confidence: 99%
“…PEH appears to be a result of a persistent reduction in peripheral vascular resistance and due to the action of vasodilators [31][32][33][34][35][36][37][38]. Halliwill's group [31,[39][40][41] demonstrated that nitric oxide (NO), prostaglandins and histamine contributes to PEH.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the baroreflex sensitivity was reported to decrease during exercise (3, 4) and after exercise (5) compared with that before exercise. Recently, Kajeker et al (10) studied the role of rostral ventrolateral medulla neurons in controlling arterial baroreflex sensitivity and reported that GABA signaling in the brain stem increased after a bout of exercise to decrease arterial baroreflex sensitivity, leading to hypotension. Moreover, microinjection of the NO synthetase inhibitor into this area increased and the NO donor SNP reduced sympathetic outflow, perhaps via an inhibitory effect on sympathoexcitatory neurons in the brain stem (28).…”
Section: Discussionmentioning
confidence: 99%